Peran Guru dalam implementasi pembelajaran berbasis kurikulum merdeka: Peran guru dalam implementasi pembelajaran berbasis kurikulum merdeka - Yuli, Yuli Yanti; Agus Pahrudin; Agus Jatmiko; Koderi (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
ABSTRACT Teachers as the main pillar in education must always follow developments in education, including in terms of curriculum. The method in this study is systematic literature review. The role of teachers in the independent curriculum is very important in educating students to be more creative, innovative and independent in their learning process. The advantage of the independent curriculum is that teachers are free to act as facilitators, providing space for each student to realize their unique potential. In order for the world of education to develop more progressively, it is necessary to develop superior skills for all people involved in education. Keywords: Role of teachers, Independent Curriculum, Learning